167k views
2 votes
Evaluate the limit of sequence below:


\displaystyle \large{\lim_(n \to \infty) (3)/(√(4n^2+2n)-2n)}
I've been getting 0 as answer. I plotted the graph and it shown that it was approaching 6 when n tends to infinity, but I couldn't figure out how to evaluate the limit like this.
Please show your work on how the answer is 6. Thank you!​

1 Answer

5 votes

Answer:

6

Explanation:

we would like to compute the following limit of a sequence below:


\displaystyle\lim_(n \to \infty) (3)/(√(4n^2+2n)-2n)

before we do so,here some formulas below which is required:


  1. \displaystyle \lim _(x \to c) (f(x))/(g(x)) = ( \displaystyle \lim _(x \to c)f(x) )/(\displaystyle \lim _(x \to c)g(x) )

finding the limit:

utilize the first formula:


( \displaystyle\lim_(n \to \infty)3)/( \displaystyle\lim_(n \to \infty)√(4n^2+2n)-2n)

finding the limit of numerator:

Any limit of a constant is equal to the constant therefore the limit of the numerator is equal to 3

finding the limit of the denominator:

rationalize it:


\displaystyle\lim_(n \to \infty) \left(√(4n^2+2n)-2n * \frac{ \sqrt{ {4n}^(2) + 2n } + 2n}{ \sqrt{{4n}^(2) + 2n } + 2n } \right)

simplify multiplication:


\displaystyle\lim_(n \to \infty) \left( \frac{ 2n}{ \sqrt{{4n}^(2) + 2n } +2n} \right)

remember that,for limits to infinity, terms less than the highest degree of the numerator or denominator can be disregarded thus we can drop 2n of the square root expression


\rm\displaystyle\lim_(n \to \infty) \left( \frac{ 2n}{ \sqrt{{4n}^(2) + 2n } + 2n} \right) \implies \lim_(x\to \infty) (2n)/(2n+2n) \implies \lim_(x\to \infty)(2n)/(4n)\implies\boxed{(1)/(2)}

since we've figured out the limit of the both numerator and denominator therefore substitute:


(3)/( (1)/(2) )

simplify complex fraction:


6

hence,


\displaystyle\lim_(n \to \infty) (3)/(√(4n^2+2n)-2n)=\boxed{6}

User Margusl
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.